2014
DOI: 10.1186/s12883-014-0224-x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza-associated MOG antibody-positive longitudinally extensive transverse myelitis: a case report

Abstract: BackgroundMyelin-oligodendrocyte glycoprotein antibody (MOG antibodies) was found in various demyelinated diseases. This is the first report of a patient with longitudinally extensive transverse myelitis with an extremely high titer of MOG antibodies after an influenza infection. This case supports the view that MOG antibodies are linked to longitudinally extensive transverse myelitis and that influenza infection might trigger the MOG antibodies.Case presentationA 32-year-old healthy male developed high fever,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
(18 reference statements)
1
35
0
Order By: Relevance
“…Our case supports this observation. Amano et al reported a case of influenzaassociated transverse myelitis in a patient positive for MOG antibodies and considered influenza infection as a possible trigger for myelitis (9). Considering that the anti-MOG antibody titers in our patient were the same before and after the brain MRI abnormalities developed, the combination of anti-MOG antibodies and an external trigger may have led to brain MRI abnormalities.…”
Section: Discussionmentioning
confidence: 88%
“…Our case supports this observation. Amano et al reported a case of influenzaassociated transverse myelitis in a patient positive for MOG antibodies and considered influenza infection as a possible trigger for myelitis (9). Considering that the anti-MOG antibody titers in our patient were the same before and after the brain MRI abnormalities developed, the combination of anti-MOG antibodies and an external trigger may have led to brain MRI abnormalities.…”
Section: Discussionmentioning
confidence: 88%
“…Post‐infectious ADEM and transverse myelitis are thought to represent an autoimmune process triggered by the infection that is hypothesized to share antigentic features with antibodies directed at myelin proteins. One patient with influenza‐associated transverse myelitis was found to have high titers of myelin oligodendrocyte glycoprotein antibodies, suggesting a pathogenic role . Additionally, one patient had recurrent ADEM after a second influenza infection 6 months after his first episode and another had recurrent ADEM after an influenza vaccination suggesting a role for genetic predisposition or formation of an immunologic mechanism …”
Section: Resultsmentioning
confidence: 99%
“…121 One patient with influenza-associated transverse myelitis was found to have high titers of myelin oligodendrocyte glycoprotein antibodies, suggesting a pathogenic role. 137 Additionally, one patient had recurrent ADEM after a second influenza infection 6 months after his first episode and another had recurrent ADEM after an influenza vaccination suggesting a role for genetic predisposition or formation of an immunologic mechanism. 132,135…”
Section: Guillain-barre Syndromementioning
confidence: 97%
“…67 Presumed parainfectious/postinfectious inflammatory myelopathies have been reported in association with a variety of viral and bacterial triggers, but a definitive inflammatory etiology and correlation with infection is often difficult to prove, and infections are also well-established triggers of other definable inflammatory myelopathies such as MS, 15 AQP4-IgG seropositive NMOSD, 68 and MOG-IgG CNS demyelinating disease. [69][70][71] Fig . 2 Imaging findings in mimickers of inflammatory myelopathies.…”
Section: Other Inflammatory Myelopathiesmentioning
confidence: 99%